'Pulse' methylprednisolone and cyclophosphamide therapy in idiopathic rapidly progressive glomerulonephritis. Issue 663 (January 1981) - Friedman, G.; Granot, H.; Koplovic, Y.; Friedlander, M.
Abstract : The clinical report of a 31-year-old man who developed acute renal failure due to idiopathic rapidly progressive glomerulonephritis is presented. Intravenous pulse methylprednisolone therapy in combination with cyclophosphamide resulted in marked improvement in renal function. The literature dealing with pulse therapy is reviewed.